Learning competencies through engineering research group experiences. (8th May 2017) - Burt, Brian A.
Abstract : Purpose: In some fields, research group experiences gained in laboratories are more influential than the classroom in shaping graduate students' research abilities, understandings of post-graduate careers and professional identities. However, little is known about what and how students learn from their research group experiences. This paper aims to explore the learning experiences of engineering graduate students in one chemical engineering research group to determine what students learned and to identify the practices and activities that facilitated their learning. Design/methodology/approach: Ethnography was used to observe the experiences of one research group in chemical engineering. Fieldwork included 13 months of observations, 31 formal interviews (16 first-round and 15 second-round interviews) and informal interviews. Fieldnotes and transcriptions were analyzed using grounded theory techniques. Findings: Research group members developed four dominant competencies: presenting research, receiving and responding to feedback, solving problems and troubleshooting problems. Students' learning was facilitated by the practices and activities of the research group (e.g. weekly full group and subgroup meetings) and mediated through the interactions of others (i.e. peers, faculty supervisor and lab manager). Originality/value: This study adds to the engineering education literature and contributes to the larger discourse on identifying promising practices and activities that improve student learning in graduate education.